Water quality and antimicrobial resistant profile of Escherichia coli isolated from dug wells used for domestic purposes - Odetoyin Babatunde; Fagbewesa Mercy; Onanuga Adebola (Intelektual Pustaka Media Utama, 2022)
The rapid spread of antimicrobial resistance (AMR) poses a significant threat to public safety. The use of water containing resistant bacteria could increase the risk of spreading AMR. This study assessed the quality of 143 dug wells used for domestic purposes in some communities in Nigeria and determined the resistance profile of isolated Escherichia coli (E. coli). The MicrobactTM identification kit was used to identify the isolates, and the susceptibility profile was evaluated using the Kirby-Bauer disc diffusion method. The combination disc technique was used to test all isolates for extended spectrum beta lactamase (ESBL) production. Polymerase chain reaction was used to identify ESBL genes, Integrons, and plasmid-mediated quinolone resistance genes. A total of 110 (76.9%) wells were contaminated by coliform bacteria. Of these, 94 (84.45%) wells yielded 202 E. coli strains. The isolates were commonly resistant to ampicillin (60.9%) but were all susceptible to meropenem. Seventy-seven (38.1%) isolates were multi-drug resistant. Two isolates harbored blaCTX-M and blaTEM separately while four (19%) ciprofloxacin-resistant isolates carried the oqxAB/aac-lb-cr gene. All isolates with resistance genes harbored class 1 and/2 Integrons. Most wells had coliform counts far above the World Health Organization’s recommended limit, indicating that they are unsafe to drink. The presence of multidrug-resistant isolates in well water poses a serious risk to consumers since it might lead to outbreaks of untreatable water-borne diseases.